A ADOÇÃO DA QUÍMICA VERDE NO ENSINO SUPERIOR BRASILEIRO - Carlos Renato Strombeck Vaz; Gildo Girotto Junior; Julio Cezar Pastre (Química Nova, 2024)
Despite being responsible for many essential products in our daily lives, the chemical industries have not given proper attention to environmental issues for a long time. In the late 90’s, Green Chemistry (GC) emerged as a field of chemistry responsible for dealing with the relationship between the products used and their effects on human health and the environment. However, the employability of GC, in practice, is still incipient due to the little importance given to this field during the training of professionals. In Brazil, without a legislation that collaborates for its insertion, GC struggles to be part of the contents studied and the curricular matrices of higher education courses. This work aimed at revisiting the subject through an analysis of whether Brazilian higher educational institutions are working on disciplines related to Green Chemistry in their courses and how they are doing so. Based on the data obtained, it was noticed that this topic is more present in elective and theoretical disciplines, mainly for postgraduate and teaching training courses, taught predominantly in public institutions located substantially in the Southeast region. Although there are interesting proposals, the number of educational institutions that promote GC in their disciplines is still considered low.